A Taxonomic Revision of Artemisia Subgenus Seriphidium (Asteraceae—Anthemideae) in China - Jin, Guang-Zhao; Sheludyakova, Mariya; Abduraimov, Ozodbek; Feng, Ying; Ge, Xue-Jun (Phytotaxa, 2025)
Based on field observation and extensive herbarium studies, a comprehensive taxonomic revision of Artemisia subg. Seriphidium in China was conducted. Twenty-nine species are recognized, four of them are endemic to China. A new species, A. neolehmanniana, is described and illustrated. Two new combinations, A. minchunensis and A. sawanensis, are proposed. Thirty names are lectotypified and two names are reduced to synonymy. Three species are listed as dubious and nine species are excluded. In addition, detailed species descriptions, distribution and habitat, phenology, nomenclatural, taxonomic notes and distribution maps of each species as well as a key to Chinese subg. Seriphidium taxa are provided.